Revolutionizing Bone Regeneration: A Comprehensive Review On Bone Grafts: Life Sciences- Dentistry - Raut, Sayali; Paul Madhu, Dr. Priyanka; Reche, Dr. Amit (International Journal of Life Science and Pharma Research, 2023)
Herbal medicines are plant-based medicines and have been documented 4000 years back. Great results have beenextracted from several studies with a minimum amount of side effects. These medicines help osteogenesis as the bone graftsobtained from such are utilized as a filler and scaffold. Such grafts are bioresorbable and do not possess any reaction like antigenantibodies. The aim is to have a comprehensive review study on bone grafts. This review article covers a combination of allaspects regarding bone grafts and their different forms of availability. The Objectives of this review are to explore various bonegrafts and to summarize them so that the reader can have enough information just by reading this article. The article givesthorough information about bone grafts and mainly focuses on several ethnopharmacological studies collected using databasessuch as Pubmed, Medline, Scopus, and Google Scholar. Regarding their osteogenic, angiogenic, anti-inflammatory, and remodelingeffects, acting on bone receptors, promoting bone metabolism, increasing mineral uptake, and supporting free radical oxidation,Chenopodium ambrosioides, Piper sarmentosum, Quadrangularis Cissus, Ricinus communis, and Radix salviae miltiorrhizaeplants were the most extensively studied in several works of literature. This article concludes that using herbal bone grafts onthe site of a defect holds promise for bone regeneration and offers an alternative to conventional therapies when they areimpractical. Very few studies have been conducted to date and this has raised interest in using herbal bone grafts.